Patients' tendency to recommend plastic surgery clinic shaped by appearance consciousness - Nurliati S. Handini; Ferdi Antonio (AOSIS, 2023)
Background: Plastic surgery services need adjustment from a patient experience perspective. However, its association with outcome quality was rarely studied. Postoperative appearance can play the role in predicting the clinic recommendations likelihood. Aim: This study is aimed to analyse recommendation likelihood (LRC) to the clinic, incorporating postoperative patient consciousness of appearance (PCA) as a mediator. Setting: Postoperative patient from two plastic surgery clinics in Jakarta, the Capital of Indonesia. Methods: Quantitative study with postoperative patient self-reported survey and cross-sectional data from 97 respondents were taken purposively. Respondent data were analysed through partial least squares structural equation modelling (PLS-SEM). Results: Five elements of patient experience had positive association with LRC (p  0.05) mediated by PCA, while PCA demonstrated a large effect on LRC (β: 0.403; p = 0.004; confidence interval [CI] = 0.173-0.671). Thus, PCA can mediate the relationship of patient experience to encourage clinic recommendations. Furthermore, healthcare by plastic surgeons showed predominant relationships followed by staff service and accessibility, suggesting those should be of utmost concern to plastic surgery patients. Conclusion: Patient experience elements have positive association with LRC mediated by PCA. Therefore, the importance of PCA as a quality outcome must be considered in quality care delivery at plastic surgery clinics. Clinic management should prioritise optimising factors contributing to PCA. Contribution: This study showed evidence that postoperative consciousness of appearance as outcome quality occurred as a mediator in patient experience relationship towards behavioural intention.